Disentangling reputation from selection effects in markets with informational asymmetries: a field experiment - Alysandratos, Theodore; Geōrganas, Sōtērēs; Sutter, Matthias (The review of economics and statistics, 2024)
In markets with asymmetric information between sellers and buyers, feedback mechanisms are important to increase market efficiency and reduce the informational disadvantage of buyers. Feedback mechanisms might work because of self-selection of more trustworthy sellers into markets with such mechanisms or because of reputational concerns of sellers. We show in a field experiment how to disentangle self-selection from reputation effects. Based on 476 taxi rides with four different types of taxis, we find strong evidence for reputation effects, but little support for self-selection effects. We discuss policy implications of our findings.
Gesehen am 19.11.2024